Serum cytokine profiles at near term-equivalent age and their association with neurodevelopmental outcomes in preterm infants: an exploratory study - Wu, Yan-Jun; Wu, Wei-Chi; Chu, Shih-Ming; Lien, Reyin; Chiang, Ming-Chou; Lee, Chien-Chung (Frontiers in Pediatrics, 2025)
BackgroundWhile early-life cytokine profiles have been linked to neurodevelopmental outcomes in preterm infants, their prognostic value is limited by clinical instability and inflammatory comorbidities in the immediate postnatal period. This study explores cytokine levels measured during a more stable developmental window—near term-equivalent age [postmenstrual age (PMA) 34–38 weeks]—and their association with neurodevelopmental outcomes.MethodsWe prospectively enrolled 35 preterm infants (birth weight, 500–1,500 g). Serum cytokine levels were measured at PMA 34, 36, and 38 weeks. Neurodevelopment was assessed at 12 months’ corrected age using standardized tools (BSID-III). Infants were classified into neurodevelopmental impairment (NDI) and non-NDI groups. Cytokine levels and their changes were compared between groups.ResultsElevated IFN-γ levels at PMA 34 weeks were associated with a higher risk of NDI. Conversely, higher levels of Eotaxin-2, IL-2, IL-11, IL-16, MIP-1δ, PDGF-BB, TIMP-2, and TNF-β at PMA 36–38 weeks were observed more frequently in the non-NDI group. The trends also differed: increased IL-17 and decreased Eotaxin-1, Eotaxin-2, IL-7, IL-16, MIP-1α, MIP-1β, PDGF-BB, and TIMP-2 between PMA 34–36 weeks, and further declines in ICAM-1, IL-7, MIP-1α, and MIP-1β by PMA 38 weeks were associated with adverse outcomes. All identified biomarkers demonstrated good discriminatory ability, particularly changes in Eotaxin-2 between PMA 34 and 36 weeks and PDGF-BB between PMA 34 and 38 weeks.ConclusionsSerum cytokine levels and their trajectories during PMA 34–38 weeks may serve as potential biomarkers for identifying preterm infants at risk of neurodevelopmental impairment. Further studies with larger cohorts are needed to clarify their interplay with preterm morbidities.